Food-based social comparisons influence liking and consumption. (1st August 2020) - Mills, Jennifer S.; Polivy, Janet; Iqbal, Ayesha
Abstract: This study examined the effects of food-based social comparisons on hedonic ratings and consumption of a meal. Participants were randomly assigned to one of three experimental conditions in which they were led to believe that they got a worse meal, a better meal, or the same meal as another participant. They then tasted and rated their own meal. Subsequent liking and ad lib food consumption were measured. Participants who were told that another person got a better meal than they did (upward comparison) liked their meal less than if they were told that another person received either the same meal as they did or a worse meal (downward comparison). Similarly, participants who were in the upward comparison condition ate less food than if they were in the control or downward comparison conditions. Consumption was mediated by liking. The results suggest that being told that someone else is eating a meal that is higher or lower in hedonic value than one's own meal induces hedonic contrast and influences liking and consumption.